(untitled) (Acta Polytechnica CTU Proceedings, 2018)
Construction applications sometimes require use of a material other than construction steel or concrete – mainly in cases, where strength to weight ratio needs to be considered. A suitable solution to this problem are structures manufactured using the 3D printing process, as they have a very good strength to weight ratio (i.e.: Ti-6Al-4V – σult = 900 MPa and ρ = 4500 kg/m3). Trabecular structures are porous structures with local material characteristics identical to their commonly manufactured counterparts, but due to their geometry, they have different global mechanical properties and are suited for special applications. We designed and manufactured six variants of these structures and subjected them to uniaxial compression tests, nanoindentation tests and subsequently evaluated their differences and elastic moduli. The values of global moduli E are in the range of 2.55 GPa – 3.55 GPa for all specimens.